Enhanced selectivity to decalin in naphthalene hydrogenation under supercritical carbon dioxide - Hiyoshi, Norihito; Miura, R.; Rode, C. V.; Sato, O.; Shirai, M. (Chemistry Letters, 2005)
A charcoal-supported rhodium catalyst was highly active and selective to decalin for the hydrogenation of naphthalene at very low temperature (333 K) under supercritical carbon dioxide.

Effect of preparation parameters on characterization and activity of Co3O4 catalyst in liquid phase oxidation of lignin model substrates - Mate, Vivek R.; Jha, Ajay; Joshi, U. D.; Patil, K. R.; Shirai, M.; Rode, C. V. (Applied Catalysis A-General, 2014)
The nano structured spinel cobalt oxide (Co3O4) was prepared via simple co-precipitation method and its catalytic activity was evaluated for the liquid phase aerobic oxidation of lignin sub structure compounds such as veratryl alcohol. Catalyst preparation parameters influenced its morphology eventually affecting its oxidation activity. Thus, nano rod shaped CO3O4 catalyst showed 75% and 38% conversion of veratryl alcohol with complete selectivity to veratryl aldehyde in toluene and water, respectively, under base free condition. The influence of reaction conditions, such as temperature, oxygen pressure and catalyst loading was studied to obtain the optimum product yield and selectivity to the desired product. Furthermore, oxidation of various sub-structures of lignin model compounds was also studied over the same catalyst which was found to be in the following order: secondary alcohol >di-substituted > tri-substituted > monosubstituted > non-substitution. The stability of the catalyst was confirmed by its successful recycle for three times. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: Coniferyl alcohol; Nano Co3O4; Sinapyl alcohol; TPR; Veratryl alcohol